Driving or driven by others? A dynamic perspective on how data-driven start-ups strategize across different network roles in digitalized business networks - Mosch, Philipp; Winkler, Corinna; Eggert, Curd-Georg; Schumann, Jan H.; Obermaier, Robert; Ulaga, Wolfgang (Industrial marketing management, 2022)
Digitalization transforms how actors conduct activities and exchange resources in business networks. Data-driven start-ups are key actors in this transformation as they are often the first to commercialize novel digital technologies and influence business networks through their strategizing. Extant Industrial Marketing & Purchasing (IMP) literature has investigated roles and strategizing in business networks. However, understanding how data-driven start-ups' specificities impact their roles and strategizing is still at its infancy. Specifically, the authors conceptually show that assumptions on how data-driven start-ups strategize contradict strategizing tenets of prior IMP literature. Therefore, previous knowledge on strategizing needs further differentiation. Addressing this research need, theories-in-use and multiple case study research on 23 data-driven start-ups is conducted to examine (1) in what network roles they operate and (2) how they strategize within and across different network roles. The study extends IMP and data-driven business model research by identifying four network roles (enabler, extender, transformer, orchestrator) and developing a specific classification framework for data-driven start-ups. Furthermore, the study shows that IMP tenets apply in specific network roles only to some extent to data-driven start-ups. Finally, three strategizing trajectories are identified, which provide a dynamic perspective to IMP literature for guiding entrepreneurs on strategizing opportunities. •This paper uncovers contradictions between start-ups' strategizing tenets from IMP and data-driven business model research.•Previous insights in IMP literature on strategizing may be not applicable to data-driven start-ups.•We describe and classify four network roles of data-driven start-ups: enabler, extender, transformer, orchestrator.•We show that IMP tenets apply to data-driven start-ups only to some extent, depending on the network role.•We include a dynamic perspective by showing three strategizing trajectories for data-driven start-ups.